Aqueous tape casting and mechanical properties of La2NiO4+δ dense membranes. Issue 1 (January 2015) - Chen, Xinzhi; Einarsrud, Mari-Ann; Grande, Tor
Abstract: An environmentally friendly aqueous tape casting process for the fabrication of La2 NiO4+ δ membranes was developed using fine powders synthesized by spray pyrolysis. Green tapes with a thickness of 30–300 μm were obtained and dense and homogeneous membranes were prepared by lamination of green tapes followed by sintering in the temperature range 1300–1420 °C. The bi-axial fracture strength of the sintered materials increased from ∼108 to ∼155 MPa decreasing the average grain size of the membranes from about 9.6 to 4.2 μm. The hardness and fracture toughness, measured by the Vickers indentation technique, also decreased with increasing grain size. The mechanical properties of La2 NiO4+ δ ceramics are discussed with focus on micro-cracking/residual stresses due to the strong crystallographic anisotropy of La2 NiO4+ δ .